Genus Diversity of Actinomycetes in Cibinong Science Center, West Java, Indonesia - YANTYATI WIDYASTUTI; PUSPITA LISDIYANTI; SHANTI RATNAKOMALA; GINA KARTINA; RONI RIDWAN; ROHMATUSSOLIHAT ROHMATUSSOLIHAT; NITA ROSALINDA PRAYITNO; EVI TRIANA; NUNUK WIDHYASTUTI; RASTI SARASWATI; RATIH DEWI HASTUTI; YULIN LESTARI; MISA OTOGURO; SHINJI MIYADOH; HIDEKI YAMAMURA; TOMOHIKO TAMURA; KATSUHIKO ANDO (Microbiology Indonesia, 2012)
Actinomycetes are microorganisms that play important role to support human health and known as soil microorganisms. The aim of the research was to describe genus diversity of actinomycetes in Cibinong Science Center (CSC), West Java. Samples for isolation were soil and plant litters. The samples were air dried and ground. We employed isolation methods: dry heat (DH), sodium dodecyl sulphates-yeast extract (SDS-YE), rehydration and centrifugation (RC), and oil separation (OS). A total of 263 isolates of actinomycetes were isolated in CSC, in 2004-2006. Totally 58, 144, 50, and 11 isolates were isolated under each isolation methods, respectively. All isolates were identified using the 16S rRNA gene sequencing method. The results showed that the isolates were belonged to the family Kineosporiaceae, Micromonosporaceae, Nocardiaceae, Pseudonocardiaceae, Streptomycetaceae, Streptosporangiaceae, Mycobacteriaceae, Nocardioidaceae, Nocardiopsaceae, and Thermomonosporaceae. There were 23 genera under those families. Homology value of the isolates based on BLAST search using 16S rRNA gene sequence data as queries showed that 136, 91, 30, and 6 isolates were ≥99, 98, 97, and ≤96%, respectively, compared to the known sequence in data base. The later 6 isolates were interesting for further identification leading to new taxa. Recognized species of Streptomyces genera under the member of the Streptomycetaceae were dominant among other isolates.